Environmental Wisdom of Organic Agriculture in Karang Anyar Village, Beringin District, Deli Serdang Regency - Sihar Pandapotan (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This research was conducted to determine and identify the wisdom of the organic farming environment in Karang Anyar Village, Beringin District, Deli Serdang Regency. As for the matters being discussed are the background of an environmentally friendly (organic) farming system, the form of environmental wisdom of organic agriculture, and the strategy of strengthening organic farming in Karang Anyar Village. The research method used is the type of qualitative research with a descriptive approach through data collection techniques such as observation and interviews. The data analysis technique uses Miles & Huberman which starts with data collection, data reduction, data presentation, and drawing conclusions. The results of the study described that organic farming in Karang Anyar Village began in 1992 and was initiated by a farmer named Sukardi. He has pioneered organic agriculture to date by forming a farmer group called Karang Anyar Farmer Group since 2008. This group produces organic rice called organic pandanus fragrant rice. The environmental wisdom found in agriculture in this village is to develop artificial fertilizers naturally by utilizing fruits such as pineapple for fermentation, starch water, neem leaves, planting colorful flowers on the edge of rice fields to divert plant pests. Product marketing is done manually and the majority of buyers are institutions/families who have autism. The farmers realize the importance of contributing to the development of the quality of life of human beings and the environment in a constant and sustainable way.